Coumarin–Tetrapyrrolic Macrocycle Conjugates: Synthesis and Applications - Ana F. R. Cerqueira; Vítor A. S. Almodôvar; Maria G. P. M. S. Neves; Augusto C. Tomé (Molecules, 2017)
This review covers the synthesis of coumarin–porphyrin, coumarin–phthalocyanine and coumarin–corrole conjugates and their potential applications. While coumarin–phthalocyanine conjugates were obtained almost exclusively by tetramerization of coumarin-functionalized phthalonitriles, coumarin–porphyrin and coumarin–corrole conjugates were prepared by complementary approaches: (a) direct synthesis of the tetrapyrrolic macrocycle using formylcoumarins and pyrrole or (b) by functionalization of the tetrapyrrolic macrocycle. In the last approach a range of reaction types were used, namely 1,3-dipolar cycloadditions, hetero-Diels–Alder, Sonogashira, alkylation or acylation reactions. This is clearly a more versatile approach, leading to a larger diversity of conjugates and allowing the access to conjugates bearing one to up to 16 coumarin units.